Study on Hypoglycaemic Effect of Spirulina platensis on Long-Evans Rats (Bangladesh Journal of Scientific and Industrial Research, 2010)
Spirulina containing high concentration of functional nutrients is emerging as an important therapeutic food. So the present study was designed to evaluate the hypoglycaemic properties of Spirulina platensis on long-evans rats. Two sets of experiment were conducted, the 1st set was compared with the effect of Spirulina platensis, glibenclamide, glucose and water after feeding 60 minutes. Glibenclamide was used as a standard reference drug. The findings clearly indicated that the oral administration of Spirulina platensis (150mg/kg b.w) significantly tended to reduce blood glucose level of rat than that of glibenclamide. In the 2nd experiment long-term hypoglycaemic effect of Spirulina platensis 0.5% and 2.5% fed with high fat high sugar containing diet and 150mg/kg b.w with normal laboratory diet was also observed. The 2nd findings also indicated that the blood glucose level was significantly decreased in both the diet when supplemented with Spirulina platensis. Key words: Diabetic mellitus; High fat diet; Hypoglycaemic; Spirulina platensis; Body weight DOI: 10.3329/bjsir.v45i2.5715Bangladesh J. Sci. Ind. Res. 45(2), 163-168, 2010